Efficacy and safety of topical herbal medicine treatment on recurrent aphthous stomatitis: a systemic review - Li CL; Huang HL; Wang WC; Hua H (Dove Medical Press, 2015)
Chun-Lei Li,1,* He-Long Huang,1,* Wan-Chun Wang,2 Hong Hua1 1Department of Oral Medicine, Peking University School and Hospital of Stomatology, Beijing, 2Department of Oral Medicine, Qingdao Stomatological Hospital, Qingdao, People’s Republic of China *These authors contributed equally to this work Abstract: This study aimed to evaluate the efficacy and safety of topical treatment with natural herbal medicines on recurrent aphthous stomatitis (RAS). Nine electronic databases were searched to identify the randomized controlled trials and clinical controlled trials that reported the potential effect of natural herbal medicines on RAS published in Chinese or English. Ulcer size and duration, and remission of pain were assessed as main outcome measures. The methodological quality of the studies was evaluated using the Cochrane Handbook for Systemic Review of Interventions and Rev Man software. Thirteen trials with a total of 1,515 patients were included in the present analysis, which showed that topical treatment with natural herbal medicines seemed to benefit RAS patients by reducing ulcer size, shortening ulcer duration, and relieving pain without severe side effects. In conclusion, there is some evidence of the efficacy of topically applied natural herbal medicines with regards to improved RAS outcome measures and fewer side effects. However, given the limitations of this study, the evidence remains insufficient. Well-designed and high-quality randomized controlled trials are required for further exploration. Keywords: recurrent aphthous stomatitis, herbal medicine, systemic review, randomized controlled trial, clinical controlled trials, oral disease